THE EFFECT OF FO2 ON THE SOLUBILITY, DIFFUSION, AND SPECIATION OF TIN IN HAPLOGRANITIC MELT AT 850°C AND 2 KBAR - Linnen R.L.; Pichavant M.; Holtz F.; Burgess S. (My University, 1995)
Diffusion profiles of tin were produced in hydrous silicate melts adjacent to cassiterite crystals; the method of Harrison and Watson (1983) was adapted to produce Sn diffusion profiles in hydrous silicate melts adjacent to cassiterite crystals at 2 kbar, 850°C, and various redox conditions, from which information on the solubility, diffusion, and speciation of Sn in silicate liquids can be obtained. The use of diffusion profiles and a hydrous, yet slightly H2O-undersaturated melt composition were chosen, in order to avoid the loss of Sn to the noble-element capsule walls. Such losses occurred at reduced conditions in the previous experimental studies on the solubility or partitioning of Sn in silicate liquids (+/-fluid phase), which probably interfered with the redox or SnO2 activity control of those experiments.The redox conditions investigated in this study were controlled by the intrinsic or an imposed fH2 in rapid-quench cold-seal and internally heated pressure vessels, and were measured by either the hydrogen sensor or Shaw membrane techniques. Cassiterite solubilities at 850°C and 2 kbar range from 28,000 ppm SnO2 at FMQ-0.84 to approximately 800 ppm at FMQ+3.12, in a haplogranitic melt with a normative (anhydrous) composition of 37.2% quartz, 28.3% orthoclase, 34.1% albite, 0.4% corundum, and 5.6 wt% H2O. For redox conditions higher than FMQ+1.5, SnO2 solubility is independent offO2 , indicating that cassiterite dissolved into the melt largely as Sn4+. By contrast at more reduced conditions, log SnO2 concentration vs. log fO2 define a slope of approximately -0.5, implying that Sn is dominantly in the 2+ valence, if γSn2+melt is constant. The solubilities obtained at reduced conditions in this study are an order of magnitude higher than previously published data (at a comparable P-T, composition and fH2 of the autoclave); the low values in the previous work are attributed to the loss of Sn to the capsule walls. The diffusion of Sn is also apparently related to fO2, ranging from approximately 10-8 cm2/s at FMQ-0.84 to 10-9 cm2/s at FMQ+3.12. This is consistent with Sn2+ behaving as a network modifier, whereas the diffusion of Sn4+ is slower, similar to other high field strength elements. The strongfO2 dependence of Sn solubility can be used to explain some magmatic tin deposits and also indicates that tin might prove useful as a marker of redox changes of a variety of magmatic systems.